2015
DOI: 10.1142/9789814675475_0013
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning Insertions and Collimation Challenges

Abstract: High-performance collimation systems are essential for operating efficiently modern hadron machine with large beam intensities. In particular, at the LHC the collimation system ensures a clean disposal of beam halos in the superconducting environment. The challenges of the HL-LHC study pose various demanding requests for beam collimation. In this paper we review the present collimation system and its performance during the LHC Run 1 in 2010-2013. Various collimation solutions under study to address the HL-LHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In section VI we evaluate the loads on the collimators in the HL-LHC, for the most pessimistic loss scenario allowed at full energy. This corresponds to a 0.2 h beam lifetime over 10 s [19,20], giving a total loss power of about 1 MW.…”
Section: Introductionmentioning
confidence: 99%
“…In section VI we evaluate the loads on the collimators in the HL-LHC, for the most pessimistic loss scenario allowed at full energy. This corresponds to a 0.2 h beam lifetime over 10 s [19,20], giving a total loss power of about 1 MW.…”
Section: Introductionmentioning
confidence: 99%
“…The smallest inner radius for halo control at the maximum LHC beam energy of 7 TeV was identified at 3.6 , where = √ is the RMS beam size, for which we assume a normalized emittance = 2.5 μm. This ensures a clearance of about 3 with respect to the nominal opening of 6.7 the primary collimators in Pt7 [15].…”
Section: Operational Conditions and Electron Beam Requirementsmentioning
confidence: 99%
“…Even if the performance of the LHC collimation system so far was very good, as stored energies in excess of 300 MJ were routinely handled without quenches triggered by beam losses on the collimation system [12][13][14], uncertainties apply to the extrapolations to conditions at the HL-LHC, with doubled bunch current, smaller emittances, and higher beam energies. Various means to improve the LHC collimation performance are therefore under investigation [15]. Some important upgrades already took place in the LHC Long Shutdown 2, which covers the period 2019-2021, with a first phase of the planned low-impedance upgrade of the betatron collimators and with the improvement of the dispersionsuppressor cleaning [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent quench test measurements [7,23] have indicated that the quench limit is somewhat higher than estimated in the past, quenches remain likely to occur with the upgraded Pb-Pb luminosity. For this reason, priority has been given to the installation of collimators in the dispersion suppressors on either side of the ALICE experiment as part of the High-Luminosity LHC upgrade [24].…”
Section: Mitigation Of Losses From Collisionsmentioning
confidence: 99%